PENGEMBANGAN E-MODUL BERBASIS PBL MENINGKATKAN NUMERASI SISWA KELAS 5 SD KABUPATEN BLITAR - Nur Salma Salsabila; Shofi Nur Amalia; Ragil Tri Oktaviani (Global Action and Education for Society, 2026)
To strengthen students numeracy competence, researchers want to make electronic learning devices, for example e-modules for Fraction Materials. This research uses the development method (R&D) with the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The results obtained from this study are in the form of e-module development products based on problem-based learning fraction materials that get validation results as material expert validation gets 92%, media expert validation gets 97%, feasibility gets 94%. In addition, the product that the researcher developed received an N-Gain score of 0.717 which indicates that this product is effective in increasing students' numeracy. Thus, it can be concluded that e-modules based on problem-based learning are declared valid, feasible and effective for increasing the numeracy of grade 5 students on fraction material.